Does the financial integration in ASEAN + 3 respond to financial cooperation agreement and influence the real sectors? - Rahman, Md S.; Shahari, Farihana (World Scientific, 2019)
This paper aims to investigate the degree of financial integration by employing Markov Switching (MS) technique. It further examines the influence of financial integration on the real sectors by employing GMM approach. The finding indicates following outcomes; (1) the financial markets of ASEAN+3 economies are weakly integrated during pre-agreement periods; (2) the degree of financial integration improves during post-agreement period in which financial integration has positive influence on the real economy; (3) higher degree of financial integration indicates a positive influence on the real economies. Finally, this study offers policy implication for stabilizing the real economy.